Transgenic mice overexpressing erythropoietin adapt to excessive erythrocytosis by regulating blood viscosity - Vogel, Johannes; Kiessling, Isabel; Heinicke, Katja; Stallmach, Thomas; Ossent, Pete; Vogel, Olga; Aulmann, Michael; Frietsch, Thomas; Schmid-Schönbein, Holger; Kuschinsky, Wolfgang; Gassmann, Max (Blood, 2003)
Severe elevation of red blood cell number is often associated with hypertension and thromboembolism resulting in severe cardiovascular complications. However, some individuals such as high altitude dwellers cope well with an increased hematocrit level. We analyzed adaptive mechanisms to excessive erythrocytosis in our transgenic (tg) mice that, due to hypoxia-independent erythropoietin (Epo) overexpression, reached hematocrit values of 0.8 to 0.9 without alteration of blood pressure, heart rate, or cardiac output. Extramedullar erythropoiesis occurred in the tg spleen, leading to splenomegaly. Upon splenectomy, hematocrit values in tg mice decreased from 0.89 to 0.62. Tg mice showed doubled reticulocyte counts and an increased mean corpuscular volume. In tg mice, plasma volume was not elevated whereas blood volume was up to 25% of the body weight compared with 8% in wild-type (wt) siblings. Although plasma viscosity did not differ between tg and wt mice, tg whole-blood viscosity increased to a lower degree (4-fold) than expected from corresponding hemoconcentrated wt blood (8-fold). This moderate increase in viscosity is explicable by the up to 3-fold higher elongation of tg erythrocytes at physiologic shear rates. Apart from the nitric oxide-mediated vasodilation we reported earlier, adaptation to high hematocrit levels in tg mice involves regulated elevation of blood viscosity by increasing erythrocyte flexibility.
September 15, 2003
Gesehen am 05.05.2021